Efficient drug delivery to hypoxic tumors using thermosensitive liposomes with encapsulated anti-cancer drug under high intensity pulsed ultrasound. (1st January 2023) - Namakshenas, Pouya; Mojra, Afsaneh
Highlights: The novelty of using short HIFU pulses to compensate for the continuous sonication drawbacks. The novelty of considering different fractions of hypoxic region as real tumor microenvironment. The novelty of noticing the thermal inertia and microstructural interaction in the TSL-HIFU system. By the expansion of hypoxic fraction to 70%, the therapeutic efficacy of conventional drug delivery is reduced up to 2 times. High acoustic powers induce coagulation necrosis in the hypoxic region and mild hyperthermia in richly vascularized regions. Abstract: Poor half-life, short circulation, systemic toxicity, insufficient accumulation, and ultimately weak therapeutic response are the most important obstacles in the conventional chemotherapy. Thermosensitive liposomes (TSLs) with encapsulated anti-cancer drug doxorubicin combined with high intensity focused ultrasound (HIFU) has the potential to overcome the shortcomings of conventional chemotherapy through targeted drug delivery. In the HIFU-TSL drug delivery system, complex physicochemical and biological processes are involved; however, many works in this field suffer from a comprehensive analysis. Regarding this, the present study has the novelty of developing an advanced multi-physical and multi-compartment model to simulate the complex processes in conventional and TSL-mediated chemotherapy paired with HIFU-induced hyperthermia. Elaborating the determinant role of tumor microenvironment is another novelty, which was underrepresented in earlier investigations and is noticed in our study through the modeling of hypoxic region. Additionally, unlike previous studies that used the classical bio-heat transfer model, this study has innovation in considering the thermal inertia as well as microstructural interactions in the bio-heat transfer equation. Last by not the least, many researchers evaded the harms of continuous irradiation, which in the present work is replaced by pulsed ultrasound as an emerging method for thermal necrosis and mild hyperthermia. The results reveal that the hypoxic region prevents efficient drug delivery due to the disruption of microvascular network and reduces chemotherapy-induced cell death. A comparison between targeted drug delivery and conventional chemotherapy suggests that TSL-mediated drug delivery leads to increased cell death by more than 100% by providing high circulation time and improved bioavailability. Besides this, increasing the acoustic power (from 3 to 8.7 W) leads to a desirable achievement, which is thermal necrosis of central tumor region and high fraction of killed cells (FKCs). The FKCs in the proposed HIFU-TSL system reaches about 58% (3 W), 60% (4.1 W), 70% (7 W), and 78% (8.7 W) at 24 h after TSL-doxorubicin administration, while this value is about 30% in the conventional chemotherapy. In conclusion, this study confirms the benefits of HIFU-TSL drug delivery system. This method has the potential to be used as a targeted drug delivery system to improve anti-cancer drug efficacy, while considerably prevents the normal tissue damage. Graphical abstract: Image, graphical abstract .